A perovskite mesocrystal semiconductor material, preparation method and application in solar cells

Through liquid-phase ligand exchange process and short-chain ligand induced self-assembly, the problems of poor conductivity and stability of perovskite nanocrystalline materials are solved, and efficient perovskite mesogenic thin film preparation and photoelectric conversion efficiency of solar cells are achieved. promote.

CN115224201BActive Publication Date: 2024-12-24SUZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210718186.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-23
Publication Date
2024-12-24
Estimated Expiration
2042-06-23

AI Technical Summary

Technical Problem

Perovskite nanocrystalline materials have problems such as poor conductivity, poor stability and cumbersome device preparation in solar cell applications. This is mainly because long-chain ligands covered on the surface hinder carrier transmission, making it difficult to promote on a large scale.

Method used

The perovskite mesogenic ink is prepared by liquid-phase ligand exchange process. By introducing short-chain ligands to exchange nanocrystal surface ligands, it induces self-assembly to form highly dispersed, stable and orderly perovskite mesogenic, achieving one-step completion Film process simplifies the film preparation process.

Benefits of technology

The conductive performance and stability of perovskite nanocrystals are improved, the device preparation process is simplified, and the preparation of perovskite mesogenic thin films is achieved with high electron coupling and efficient, which is improved the photoelectric conversion efficiency of solar cells to 14.04%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115224201B_ABST
    Figure CN115224201B_ABST
Patent Text Reader

Abstract

The present invention relates to a perovskite mesocrystal semiconductor material, a preparation method and an application in solar cells. The surface ligands are removed by adding an initiator that can react mildly with oleic acid and oleylamine ligands on the surface of perovskite nanocrystals, and then short-chain organic ligands are introduced to induce material self-assembly to obtain an ordered nanoparticle superstructure with a mesoscopic scale of tens of nanometers to several microns. The present invention uses initiators and organic ligands to regulate the surface chemical environment of nanocrystals through solution-phase ligand exchange, which can effectively exchange insulating ligands on the surface of nanocrystals without destroying the crystal structure; the perovskite mesocrystal material with an ordered mesoscale structure is prepared by introducing short-chain ligands to induce nanocrystal self-assembly; highly dispersed high-stability mesocrystal conductive ink is prepared by solvent selection, and one-step spin coating or scraping film formation can be achieved without complex layer-by-layer deposition process and complicated ligand exchange process, simplifying the device preparation process; the prepared perovskite mesocrystal solar cell achieves a device efficiency of more than 14%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a perovskite mesocrystal semiconductor material, a preparation method and application in a solar cell, and belongs to the technical field of photoelectric materials. Background Art

[0002] Mesocrystals are three-dimensional ordered assemblies of nanocrystals connected by organic bridges, partially by organics or partially by themselves, or completely by themselves, with mesoscopic dimensions (1-1000 nm). They exhibit properties similar to single crystals, effectively reducing the recombination probability of carriers in the process of internal transmission of the material. Oxide mesocrystal semiconductor materials (such as ZnO, TiO2, Al2O3, SnO2, etc.) and lead sulfide mesocrystal semiconductor materials (such as CdS / CdSe, PbS, etc.) synthesized by hydrothermal or solvothermal methods have shown great application potential in the fields of photocatalysis, solar cells and ion batteries due to their unique optoelectronic properties.

[0003] Perovskite semiconductors are a new type of optoelectronic star material. They are widely used in solar cells, luminescence, light detection, catalysis and other fields due to their advantages such as large defect tolerance, long carrier diffusion length and adjustable band gap. However, there are few studies on the mesocrystalline structure of this material, which is due to the poor structural stability caused by the ionicity of perovskite materials. In 2015, Professor Kovalenko synthesized perovskite nanocrystals for the first time by hot injection (see reference: L.Protesescu, S. Yakunin, MI Bodnarchuk, F. Krieg, R. Caputo, CH Hendon, RX Yang, A. Walsh, MV Kovalenko, Nano Lett. 2015, 15, 3692.). Due to the size effect, they have large surface stress. In addition, due to the presence of long-chain ligands on the surface, perovskite nanocrystals show higher structural stability than bulk materials, which provides an important opportunity for the preparation and study of perovskite mesocrystalline semiconductors and perovskite superlattice materials.

[0004] At present, the surface of perovskite nanocrystals prepared by the widely used hot injection method is usually coated with long-chain insulating oleic acid and oleylamine ligands, resulting in a large dielectric layer between the nanocrystals, which hinders the transmission of carriers and makes it difficult to directly apply this material to optoelectronic devices; the layer-by-layer deposition process and cumbersome solid-phase ligand exchange are required in the thin film preparation process, which greatly increases the difficulty of surface ligand regulation and the complexity of device preparation, making it difficult to promote and apply perovskite nanocrystals on a large scale. Summary of the invention

[0005] The present invention aims at the shortcomings of existing perovskite nanocrystalline materials such as poor conductivity, poor stability and complicated device preparation, and adopts a liquid phase ligand exchange process to prepare perovskite mesocrystal ink and form a film in one step, thereby providing a perovskite mesocrystal semiconductor material, a preparation method and an application in solar cells.

[0006] The technical solution to achieve the purpose of the present invention is to provide a method for preparing a perovskite mesocrystal semiconductor material, comprising the following steps:

[0007] (1) dispersing perovskite nanocrystals coated with oleic acid and oleylamine long-chain ligands in a solvent to prepare a perovskite nanocrystal solution with a concentration of 20 to 100 mg / ml; the solvent comprises one of n-hexane, n-octane, toluene, chloroform, or any combination thereof;

[0008] (2) adding an initiator dropwise to the perovskite nanocrystal solution prepared in step (1) to carry out a liquid phase ligand exchange reaction, and then centrifuging to obtain perovskite mesocrystals; the initiator comprises one of dipropylamine, dibutylamine, and dipentylamine, or any combination thereof;

[0009] (3) Adding a short-chain ligand to a solvent to prepare a ligand solution with a concentration of 0.00001 to 1 M, wherein the short-chain ligand comprises one of formamidine thiocyanate (FASCN), methylamine thiocyanate (MASCN), phenylethylamine (PEA), amphetamine, triphenylphosphine (TPP), triphenylphosphine oxide (TOP), triphenyl phosphite (TPPI), or any combination thereof; the solvent used comprises one of toluene, chlorobenzene, and chloroform, or any combination thereof; adding the ligand solution to the perovskite mesocrystal prepared in step (2), mixing thoroughly, and obtaining a perovskite mesocrystal ink.

[0010] The perovskite mesocrystal ink prepared as described above is subjected to a one-step spin coating, spray coating or blade coating process to prepare a perovskite mesocrystal film.

[0011] The present invention provides a method for preparing a perovskite mesocrystal semiconductor material, wherein the preferred process conditions are: a liquid phase ligand exchange reaction time of 10 seconds to 10 minutes; a centrifugal treatment condition of 500 to 4000 rpm; and a volume ratio of an initiator to a perovskite nanocrystal solution of 0.00001 to 1.

[0012] The perovskite mesocrystal ink provided by the present invention has a perovskite mesocrystal concentration of 10-500 mg / ml.

[0013] The technical solution of the present invention also includes a perovskite mesocrystal ink and a perovskite mesocrystal film obtained according to the above preparation method.

[0014] The application of the perovskite mesocrystal ink provided by the present invention in the light-absorbing layer of a solar cell, wherein the solar cell comprises a conductive glass substrate, an electron transport layer, a perovskite mesocrystal light-absorbing layer, a hole transport layer and a metal electrode, and is characterized by comprising the following steps:

[0015] (1) Preparing an electron transport layer on a conductive glass substrate;

[0016] (2) A hybrid perovskite thin film light absorbing layer with a thickness of 50-800 nm is prepared on the electron transport layer by a one-step spin coating or blade coating process;

[0017] (3) A hole transport layer with a thickness of 30-80 nm is prepared by spin coating on the light absorbing layer;

[0018] (4) A metal electrode is deposited on the hole transport layer using a vacuum coating process to obtain a perovskite mesocrystalline solar cell.

[0019] The present invention provides a perovskite mesocrystal semiconductor material, wherein the perovskite mesocrystal is an ordered nanoparticle superstructure with a mesoscopic scale ranging from tens of nanometers to several micrometers, which is self-assembled by perovskite nanocrystals in a ligand-induced manner, and the crystal structure is ABX3, wherein A is formamidine (CH(NH2)2 + ) or methylamine (CH3NH3 + ) organic cation, B is Pb 2+ or Sn 2+ , X is I - Br - , Cl - , or a mixture thereof; the present invention adopts a technical solution of adding an initiator and a short-chain ligand in the solution phase, and the ligands on the surface of the nanocrystal are exchanged to induce self-assembly, thereby realizing the preparation of a perovskite mesocrystalline material with an ordered mesoscale structure.

[0020] The principle of the present invention is: adding dipropylamine and other polar organic molecular initiators that can react mildly with the surface ligands of the nanocrystals to the perovskite nanocrystal solution to remove the surface ligands of the nanocrystals without destroying the crystal structure of the material; after a period of liquid phase ligand exchange reaction, the surface ligands of the nanocrystals are largely removed, thereby inducing aggregation and assembly to produce hybrid perovskite mesocrystals with a size of tens of nanometers to several micrometers; and then separating the obtained perovskite mesocrystals through centrifugal treatment; the obtained perovskite mesocrystals cannot be dispersed in solvents with small dielectric constants such as n-hexane and n-octane because the surface ligands are largely removed and the assembly size is large; the present invention adopts the method of adding short-chain ligands, short-chain organic amines or organic phosphine ligands to non-polar solvents such as toluene to prepare a ligand solution, which is added to the perovskite mesocrystals for full mixing; by controlling the concentration of the short-chain ligands and the volume of the solution, a perovskite mesocrystal ink with a concentration of 10 to 500 mg / ml, high dispersion stability (more than 2 months) and high electronic coupling can be obtained.

[0021] The present invention adopts appropriate surface chemical regulation means to realize liquid-phase ligand exchange of perovskite nanocrystals, and then prepares perovskite mesocrystal conductive ink by introducing new ligands to induce self-assembly of perovskite nanocrystals, and the perovskite mesocrystal ink prepared by the present invention can be directly prepared into a perovskite mesocrystal film with high electron coupling by one-step spin coating, spray coating, scraping coating, etc. The present invention provides a new film-forming process for preparing perovskite mesocrystal films for optoelectronic devices, without the need for complex layer-by-layer deposition processes and cumbersome solid-phase ligand exchange processes, and the obtained perovskite mesocrystal films can be used for photosensitive layers of solar cells, photodetectors, and light-emitting diodes, which has important practical significance for the commercial application of perovskite semiconductor materials in the optoelectronic field.

[0022] Compared with the prior art, the technology of the present invention has the following outstanding features:

[0023] 1. The present invention provides a mild perovskite nanocrystal liquid phase ligand exchange process by selecting an initiator that can mildly react with the surface ligands of the perovskite nanocrystals; at the same time, by introducing new short-chain, conductive ligands to passivate surface defects and induce nanocrystals to self-assemble into highly ordered mesocrystals, the conductivity and stability of the perovskite nanocrystals are improved, thereby realizing the preparation of high-performance perovskite mesocrystal ink.

[0024] 2. The ink prepared based on the present invention provides a one-step film-forming process that is compatible with spin coating, spray coating, scraping coating and other technical means, which solves the cumbersome layer-by-layer deposition process and difficult-to-control solid-phase ligand exchange in the preparation process of traditional perovskite nanocrystal devices, thereby simplifying the device preparation process and facilitating the commercial promotion of perovskite nanocrystals.

[0025] 3. The present invention selected near-infrared absorbing perovskite nanocrystals and prepared high-efficiency perovskite mesocrystal solar cells, achieving a record photoelectric conversion efficiency of 14.04% for the application of this material in solar cells (the record of the prior art is 13.2%, see literature: J. Mater. Chem. A, 2020,8, 8104-8112), proving the feasibility of the application of this material and technical means in optoelectronic devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 A transmission electron microscope (TEM) comparison diagram of the perovskite mesocrystal prepared in Example 1 of the present invention and a standard perovskite nanocrystal;

[0027] Figure 2 A comparison of dynamic light scattering of perovskite mesocrystals prepared in Example 2 of the present invention in different solvents;

[0028] Figure 3A schematic diagram of the device structure of a perovskite mesogenic solar cell provided in Example 4 of the present invention;

[0029] Figure 4 This is a current density-voltage (JV) curve of the perovskite mesogenic solar cell prepared in Example 4 of the present invention;

[0030] In the figure, 1. Conductive glass substrate; 2. Electron transport layer; 3. Light absorption layer; 4. Hole transport layer; 5. Metal electrode. DETAILED DESCRIPTION

[0031] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0032] Example 1

[0033] This embodiment provides a method for preparing a hybrid FAPbI3 perovskite mesocrystal ink, and the specific steps are as follows:

[0034] Step 1: Disperse the FAPbI3 perovskite nanocrystals coated with oleic acid and oleylamine synthesized by hot injection (the synthesis method is described in the literature: Nat. Commun. 2019, 10, 2842) in a n-hexane solution to prepare a nanocrystal solution with a concentration of 30 mg / ml for later use;

[0035] Step 2: Using dipropylamine as an initiator, 30 μl of dipropylamine was added dropwise to 20 ml of the nanocrystal solution and allowed to stand for about 10 seconds, and the nanocrystals began to aggregate and assemble;

[0036] Step 3, centrifuging the product obtained in step 2 at a speed of 1000 rpm for 2 minutes to separate the settled mesocrystals, pouring out the liquid after centrifugation, retaining the obtained solid, i.e., the hybrid perovskite mesocrystal, and weighing it;

[0037] Step 4: adding the hybrid perovskite mesocrystal obtained in step 3 into the dispersant toluene, which has a good dispersing effect, to prepare the perovskite mesocrystal ink.

[0038] See attached Figure 1 , which is a transmission electron microscope (TEM) comparison of the perovskite mesocrystal prepared in this embodiment and the standard perovskite nanocrystal; in the figure, (a) shows the morphology of the standard FAPbI3 perovskite nanocrystal without liquid phase ligand exchange, and (b) shows the morphology of the hybrid perovskite mesocrystal self-assembled by surface ligand induced provided in this embodiment. Comparison of (a) and (b) shows that the nanocrystal aggregation and assembly are induced after the initiator reacts with the surface ligand of the perovskite nanocrystal.

[0039] Example 2

[0040] This embodiment provides a hybrid MAPbI3 perovskite mesocrystal ink, and its preparation method and specific steps are as follows:

[0041] Step 1: Disperse MAPbI3 perovskite nanocrystals coated with oleic acid and oleylamine synthesized by hot injection method (for the synthesis method, refer to Chinese invention patent CN 114276800A) in n-hexane solution to prepare a nanocrystal solution with a concentration of 30 mg / ml for standby use;

[0042] Step 2: Use dipropylamine as an initiator, add 40 microliters of dipropylamine to 20 milliliters of nanocrystal solution, let it stand for about 10 seconds, and the nanocrystals begin to aggregate and assemble;

[0043] Step 3: Separate the settled mesocrystals by centrifugation at 1500 rpm for 3 minutes, pour out the supernatant, retain the obtained solid and weigh it;

[0044] Step 4: The obtained hybrid MAPbI3 perovskite mesocrystal cannot be dispersed into solvents with smaller dielectric constants such as n-hexane and n-octane because the surface ligands have been largely removed. The dispersion stability is tested by comparing non-polar solvents with different dielectric constants including n-hexane, chlorobenzene, chloroform, toluene, etc. Toluene is used as the dispersant to obtain the perovskite mesocrystal ink with the best dispersion stability.

[0045] See attached Figure 2 , which is a dynamic light scattering comparison diagram of the perovskite mesocrystal prepared in this example in different solvents; in the figure, the dispersibility of non-polar solvents with different dielectric constants such as n-hexane, chlorobenzene, chloroform, and toluene on MAPbI3 mesocrystal (concentration is 20 mg / ml) is compared. Figure 2 It can be seen that the perovskite mesocrystals obtained by using n-octane have poor dispersibility, while other solvents are acceptable, and the hybrid perovskite mesocrystals dispersed by toluene have better stability.

[0046] Example 3

[0047] This embodiment provides a method for preparing a perovskite mesogenic film using a hybrid FAPbI3 perovskite mesogenic ink by a one-step spin coating process, and the specific steps are as follows:

[0048] Step 1: Disperse the surface-coated FAPbI3 perovskite nanocrystals with oleic acid and oleylamine synthesized by hot injection in a n-hexane solution to a concentration of 30 mg / ml for later use;

[0049] Step 2: Use dibutylamine as an initiator, add 30 microliters of dibutylamine to 20 milliliters of nanocrystal solution, let it stand for about 10 seconds, and the nanocrystals begin to aggregate and assemble;

[0050] Step 3: Separate the settled mesocrystals by centrifugation at 2000 rpm for 2 minutes, pour out the supernatant, retain the obtained solid and weigh it;

[0051] Step 4: Dissolve TPP as a new ligand in toluene at a concentration of 1.5 mg / ml, and then add the solution to the obtained solid to make the required concentration to obtain a hybrid FAPbI3 perovskite mesocrystal ink with high stability, high electronic coupling, and low surface defect states after ligand exchange.

[0052] In this embodiment, the hybrid perovskite mesocrystal prepared in step 3 is dispersed in toluene as a solvent, and perovskite mesocrystal inks of different concentrations are prepared according to the ink concentrations (mg / ml) provided in Table 1. By adjusting the spin coating rate, high-quality perovskite films of different thicknesses are prepared by a one-step spin coating process.

[0053] The film thickness parameters prepared by spin coating with different concentrations of perovskite mesocrystal ink and different rotation speeds are shown in Table 1.

[0054] Table 1

[0055] Ink concentration (mg / ml) Spin coating speed (rpm) Film thickness (nm) 100 1000 150±20 200 1000 300±20 200 2000 200±20 300 1000 400±20 300 2000 350±20

[0056] The film provided in this embodiment can be used for the photosensitive layer of optoelectronic devices such as solar cells, photodetectors, light-emitting diodes, memristors or field-effect transistors, and has high application value.

[0057] At present, the layer-by-layer deposition process is a necessary process for preparing perovskite nanocrystal solar cells in the prior art (see literature: Science 2016, 354, 92; Sci. Adv. 2017, 3, eaao4204); the method for preparing the thin film of the perovskite mesocrystal ink provided by the present invention can obtain a thin film of the required thickness in just one step, and the process is simple, avoiding the cumbersome layer-by-layer deposition process and the complicated solid-phase ligand exchange process. The method provided by the present invention can also be extended to scraping and spraying processes, and is compatible with large-area printing technology.

[0058] Example 4

[0059] This embodiment provides a method for preparing a hybrid FAPbI3 perovskite mesocrystal solar cell, and achieves a record efficiency of the material solar cell, and its photoelectric conversion efficiency is significantly improved. Figure 3 , is a schematic diagram of the device structure of a solar cell, such as Figure 3 As shown, an electron transport layer 2, a perovskite nanocrystal light absorption layer 3, a hole transport layer 4 and a metal electrode 5 are sequentially prepared on a conductive glass substrate 1. The preparation of the battery includes the following steps:

[0060] Step 1: ultrasonically clean the fluorine-doped tin oxide (FTO) conductive glass with detergent, deionized water, isopropanol, and acetone in sequence; prepare a dense TiO2 film with a thickness of about 40 nanometers on the clean conductive glass substrate 1 by chemical water bath deposition to obtain an electron transport layer 2, and anneal at 200° C. for 30 minutes;

[0061] Step 2: In a dry air atmosphere, a one-step spin coating method is used to spin-coat a 200 mg / ml FAPbI3 toluene solution prepared in Example 3 as a perovskite mesogen ink on a FTO / TiO2 substrate at 1000 rpm and 2000 rpm for 15 seconds and 20 seconds, respectively. The film is treated with a FASCN solution of methyl acetate for 5 seconds to obtain a highly electron-coupled perovskite film light-absorbing layer 3 with a thickness of about 300 nm.

[0062] Step 3: Spin-coat polymer PTAA on the light absorbing layer 3 to prepare a hole transport layer 4. Dissolve PTAA in toluene to prepare a solution with a concentration of 15 mg / ml, and spin-coat at 3000 rpm for 40 seconds to form a hole transport layer with a thickness of about 70 nm.

[0063] Step 4: Vacuum thermal evaporation of metal electrode 5, MoO X The thickness of Ag is 8 nm and 120 nm respectively, and a complete FAPbI3 perovskite mesocrystalline solar cell is obtained.

[0064] See attached Figure 4 This example provides a current density-voltage (JV) curve of a perovskite solar cell prepared by using a solution-phase ligand exchange, TPP surface modification and a one-step spin coating process using hybrid FAPbI3 perovskite nanocrystals as the light-absorbing layer; at AM 1.5, 100 mV / cm 2 Under standard test conditions, the short-circuit current density of the device was measured to be 17.28 mA / cm 2 , the open circuit voltage is 1.156 V, the fill factor is 0.703, and the photoelectric conversion efficiency is 14.04%, while the current record efficiency of this material is 13.2% (see literature: J. Mater. Chem. A , 2020,8, 8104-8112).

Claims

1. A method for preparing a perovskite mesocrystal semiconductor material, characterized in that The steps include: (1) dispersing perovskite nanocrystals coated with oleic acid and oleylamine long-chain ligands in a solvent to prepare a perovskite nanocrystal solution with a concentration of 20 to 100 mg / ml; the solvent comprises one of n-hexane, n-octane, toluene, chloroform, or any combination thereof; (2) adding an initiator dropwise to the perovskite nanocrystal solution prepared in step (1) to carry out a liquid phase ligand exchange reaction, and then centrifuging to obtain perovskite mesocrystals; the initiator comprises one of dipropylamine, dibutylamine, and dipentylamine, or any combination thereof; (3) Adding a short-chain ligand to a solvent to prepare a ligand solution with a concentration of 0.00001 to 1 M, wherein the short-chain ligand comprises one of formamidine thiocyanate (FASCN), methylamine thiocyanate (MASCN), phenylethylamine (PEA), amphetamine, triphenylphosphine (TPP), triphenylphosphine oxide (TOP), triphenyl phosphite (TPPI), or any combination thereof; the solvent used comprises one of toluene, chlorobenzene, and chloroform, or any combination thereof; adding the ligand solution to the perovskite mesocrystal prepared in step (2), mixing thoroughly, and obtaining a perovskite mesocrystal ink.

2. The method for preparing a perovskite mesocrystal semiconductor material according to claim 1, characterized in that: The liquid phase ligand exchange reaction time is 10 seconds to 10 minutes.

3. The method for preparing a perovskite mesocrystal semiconductor material according to claim 1, characterized in that: The centrifugal treatment condition is 500-4000 rpm.

4. The method for preparing a perovskite mesocrystal semiconductor material according to claim 1, characterized in that: The volume ratio of the initiator to the perovskite nanocrystal solution is 0.00001-1.

5. The method for preparing a perovskite mesocrystal semiconductor material according to claim 1, characterized in that: The perovskite mesocrystal ink has a perovskite mesocrystal concentration of 10 to 500 mg / ml.

6. A method for preparing a perovskite mesocrystal semiconductor material, characterized in that: The perovskite mesocrystal ink prepared according to claim 1 is used to prepare a perovskite mesocrystal film by a one-step spin coating, spray coating or scraping coating process.

7. A perovskite mesocrystal ink obtained by the preparation method according to claim 1.

8. A perovskite mesocrystal film obtained by the preparation method according to claim 6.

9. A use of the perovskite mesocrystal ink according to claim 7 in a light-absorbing layer of a solar cell, wherein the solar cell comprises a conductive glass substrate, an electron transport layer, a perovskite mesocrystal light-absorbing layer, a hole transport layer and a metal electrode, characterized in that The steps include: (1) Preparing an electron transport layer on a conductive glass substrate; (2) A hybrid perovskite thin film light absorbing layer with a thickness of 50-800 nm is prepared on the electron transport layer by a one-step spin coating or blade coating process; (3) A hole transport layer with a thickness of 30-80 nm is prepared by spin coating on the light absorbing layer; (4) A metal electrode is deposited on the hole transport layer using a vacuum coating process to obtain a perovskite mesocrystalline solar cell.